Modern Psycho-Aesthetic Discussion of O‘Neill‘s Strange Interlude - Foroozani, Seyedeh Sara; Hadaegh, Bahee (International Journal of Psychosocial Rehabilitation, 2025)
Tragedy in modern American drama is preoccupied with the study of creativity and loss, as the two prove strong solidarity in aesthetic discussions. Adorno recognizes certain unbalanced relationships between nature (modern society) and an individual as the ultimate source of suffering, central to an understanding of aesthetic expression. Whereas, art endeavors to transcend its inherent experience of suppression and pain through negating the reality of loss; Adorno’s Truth Content associates itself with a non-discursive form of experience that refers to the transient nature of truth, compromising a self-reflexive, propositional and subjective nature, to which all aesthetic questions terminate. Correspondingly, in psychoanalytic debates, Jacques Lacan develops his theory based on unconscious operations and transient essence of meaning in different contexts. Lacan introduces the Imaginary Order, the Symbolic Order and the Real Order, as concerned with the haunting experiences of loss in unconscious and the concept of objet petit a, so as to ponder on the uninterpretable and unattainable existential domains. The Real Order resists the Imaginary and the Symbolic, claiming to have existed beyond language and prior to all, in a way that no media can embody the Real; it can only point to the Real. Since the Truth Content and the Real Order are attached to the experience of loss and repressed desires, Eugene O’Neill seems to utilize aesthetic negation to study a new form of autobiographical realism, interested in unmasking the multilayered reality. Accordingly, for the first time in the history of psycho-aesthetic studies, the present research aims to provide a fluid psychological analysis of Eugene O’Neill’s heroin, originated from the Real Order so as to reveal the reason beyond her romantic negations and to ponder on the degree to which Lacanian Real Order contributes to Theodor Adorno’s concept of Truth Content in modern drama.